2011
DOI: 10.1002/joc.2316
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulations associated to the interannual variability of cumulonimbus cloud frequency in the southern part of Romania

Abstract: Especially in summer time, Romania is affected by deep convections associated with severe weather phenomena (hail, wind gusts, flash floods, frequent thunder).The interannual variability of the Cb (cumulonimbus) cloud frequency recorded at 20 weather stations from the southern part of Romania in the 1961-2007 interval was investigated in connection with the atmospheric circulation variability.Using the Canonical Correlation Analysis (CCA) three types of atmospheric circulations have been identified that contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The data using a block maxima approach, with both yearly and seasonal blocks, are analyzed. The climatology of extreme rainfall over this area is unimodal, with a large peak during late spring and summer seasons (Figure 3), during which the heavy rainfall is mostly associated with convective activity (Sun et al 2001; Antonescu and Burcea 2010; Paraschivescu et al 2011).…”
Section: Methodsmentioning
confidence: 97%
“…The data using a block maxima approach, with both yearly and seasonal blocks, are analyzed. The climatology of extreme rainfall over this area is unimodal, with a large peak during late spring and summer seasons (Figure 3), during which the heavy rainfall is mostly associated with convective activity (Sun et al 2001; Antonescu and Burcea 2010; Paraschivescu et al 2011).…”
Section: Methodsmentioning
confidence: 97%
“…Obtaining synoptic patterns associated with particular weather conditions contributes to a wide range of purposes (climatological studies, weather forecasting, biometeorology, environmental studies), and in recent years several authors have established the impact of different circulation types on convective activity (Kolendowicz, 2006;Paraschivescu et al, 2012), and lightning activity (Tomás et al, 2004;Mikus et al, 2012). In particular, Ramos et al (2011) reported that the highest number of CG lightning flashes in Portugal was associated with northeastern circulation over Portugal due to an extension * Correspondence to: Dr. L. Rivas Soriano, Departamento de Física de la Atmósfera, Facultad de Ciencias, Universidad de Salamanca, Pl.…”
Section: Introductionmentioning
confidence: 99%
“…The winter season is characterized by large‐scale weather patterns that are better captured by the climate indices, in particular NAO. On the other hand, summertime precipitation is associated with convective activity (Paraschivescu et al , 2011), that is more spatially localized and less directly related to NAO or SOI. Moreover, different covariates are retained depending on the season, with NAO that is mostly related to fall–winter rainfall, while SOI to spring–summer rainfall (see also Busuioc and von Storch, 1996; Van Oldenborgh et al , 2000; Mares et al , 2002; Lloyd‐Hughes and Saunders, 2002; Tomozeiu et al , 2005).…”
Section: Resultsmentioning
confidence: 99%